Over-the-scope clip vs epinephrine with clip for first-line hemostasis in non-variceal upper gastrointestinal bleeding: a propensity score match analysis - Mangiafico, Santi; Pigò, Flavia; Bertani, Helga; Caruso, Angelo; Grande, Giuseppe; Sgamato, Costantino; Manta, Raffaele; Conigliaro, Rita (Endoscopy International Open, 2020)
Background and study aims The over-the-scope clip (OTSC) is a novel tool used to improve the maintenance of hemostasis for non-variceal upper gastrointestinal bleeding (NVUGIB); however, studies on the comparison with “conventional” techniques are lacking. In this study, we aimed to compare first-line endoscopic hemostasis achieved using conventional techniques with that achieved using OTSC placement for NVUGIB.Patients and methods From January 2007 to March 2018, 793 consecutive patients underwent upper endoscopy with the hemostasis procedure. Among them, 327 patients were eligible for inclusion (112 patients had OTSC placement and 215 underwent conventional hemostasis). After propensity score matching and adjustment for confounding factors, 84 patients were stratified into the “conventional” group and 84 into the OTSC group. Patient characteristics and outcomes (rebleeding rate, mortality rate within 30 days, and adverse events) were compared between the two groups.Results In the unmatched cohort, hemostasis with OTSC was more frequent in cases of duodenal ulcers with Forrest Ia to IIa and in patients with a higher Rockall score compared with the “conventional group”. In the matched cohort, 93 % of the patients in the “conventional group” underwent hemostasis with epinephrine + through-the-scope clip. Rebleeding events were significantly less frequent in the OTSC group (8 % vs 20 %, 95 %CI 3 – 16 vs 12 – 30; P = 0.02); however, the mortality rate in the two groups was not significantly different (6 % vs 2 %, 95 %CI 1 – 8 vs 2 – 13; P = 0.4).Conclusions OTSC is a safe and effective tool for achieving hemostasis, and we recommend its use as the first-line therapy for lesions with a high risk of rebleeding and in patients with a high risk Rockall score.